2004
DOI: 10.1161/01.cir.0000109499.00587.ff
|View full text |Cite
|
Sign up to set email alerts
|

N -Acetylcysteine Prevents the Deleterious Effect of Tumor Necrosis Factor-α on Calcium Transients and Contraction in Adult Rat Cardiomyocytes

Abstract: Background-The negative effect of tumor necrosis factor-␣ (TNF-␣) on heart contraction, which is mediated by sphingosine, is a major component in heart failure. Because the cellular level of glutathione may limit sphingosine production via the inhibition of the Mg-dependent neutral sphingomyelinase (N-SMase), we hypothesized that cardiac glutathione status might determine the negative contractile response to TNF-␣. Methods and Results-We examined the effects of TNF-␣ in isolated cardiomyocytes obtained from co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 33 publications
5
65
0
Order By: Relevance
“…H 2 0 2 and lipid peroxidation by-products were quantified in LV homogenates using the Amplex Red Hydrogen Peroxide Kit (A22188) (Molecular Probes) and the Lipid peroxidation kit (Calbiochem), respectively. N-SMase activity was determined in LV homogenates as previously described [11].…”
Section: Homogenate Preparation and Biochemical Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…H 2 0 2 and lipid peroxidation by-products were quantified in LV homogenates using the Amplex Red Hydrogen Peroxide Kit (A22188) (Molecular Probes) and the Lipid peroxidation kit (Calbiochem), respectively. N-SMase activity was determined in LV homogenates as previously described [11].…”
Section: Homogenate Preparation and Biochemical Assaysmentioning
confidence: 99%
“…We previously reported that glutathione status determines TNF-α adverse effects in heart [11,12]. Herein we addressed the question as to whether glutathione deficiency might be causally linked to the exacerbated TNF-α activation occurring in well-established CHF, as this was observed in several other chronic diseases including HIV infection [13,14], neurodegeneration [1,15], muscular fatigue [14], rheumatoid arthritis [3] and chronic lung diseases [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perfusion of isolated rabbit hearts with hydrogen peroxide increased cytosolic calcium concentration (Corretti et al, 1991) and TNF-α or ischemia induce changes in calcium handling that are normalized by application of ROS scavengers (Cailleret et al, 2004;Dworschak et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…One of the important downstream signal transduction mechanisms is activation of two different sphingomyelinases (with different localization), which are called neutral and acid sphingomyelinase (38,49 Á51). The sphingomyelinases cleave sphingomyelin to ceramide and phosphocholine, and ceramide (N-acylsphingosine) can subsequently be degraded to a fatty acid'/sphingosine; these molecules (especially ceramide and sphingosine) may be regarded as functioning as second messengers of TNF-a (40,50). Ceramide is important not only as a signal molecule in its own right, but also as a precursor of other molecules that have signal function, such as lactosylceramide (51).…”
Section: Evolution Of Virulence Properties In Influenza Virusesmentioning
confidence: 99%